Cseresznyelégy elleni endoterápiás kezelés - Gyuris, Rita; Sörös, Csilla; Gutermuth, Ádám; Szabó, Árpád (GEORGIKON FOR AGRICULTURE, 2023)
The European cherry fruit fly (Rhagoletis cerasi) can cause up to 100% damage in Hungary and in some other countries. This fly makes the crop completely unusable for export and fresh consumption. Smaller trees can be successfully protected by spraying in the intensive cultivation. But spraying is often applied in unnecessary amounts, what pollutes the environment and most of the spraying does not reach the target pests. Injection affects only the tree organisms, environmentally friendly, and we can use low doses of the active ingredient to kill pests. In our work, we select and formulate pesticides into injectable formulations, evaluate the experiment from an entomological view, and then measure the active ingredient residue in the fruit. When trees were treated with 3.96 g active flupyradifurone ingredient, we reached 99% protection against the cherry fruit fly. And when we treated the trees with 0.56 g and 1.12 g acetamiprid, the protection were 97% in both cases. The insecticidal effect was also lower with lower dose treatments. Flupyradifurone ingredient residue in the cherry crop were ranged from 51.42 ng/g to 400.37 ng/g and the acetamiprid ingredient residue were ranged from 6.6 ng/g to 176.96 ng/g, depending on the treatment dose.
Keywords: Cherry fruit fly; Rhagoletis cerasi; trunk injection; acetamiprid; flupyradifurone